An ultrahigh thermal conductive graphene flexible paper. Issue 43 (27th October 2017) - Ding, Jiheng; Zhao, Hongran; Wang, Qiaolei; Dou, Huimin; Chen, Hao; Yu, Haibin
Abstract : Preparation of ultrahigh thermal conductive graphene flexible paper based on ball milling-exfoliated graphene nanosheets. Abstract : Graphene nanosheets (GNSs) possess outstanding conductivity, good thermal and chemical stabilities and desirable mechanical strengths. However, the unfunctionalized GNSs are hydrophobic and insoluble in water, which limits their application in many technological areas. Herein, we report a design strategy to exfoliate few-layered aqueous dispersible graphene by a simple ball-milling technique. The modifier of sodium lignosulfonate (LS) enables to synthesize LS-decorated GNSs from natural graphite based on the strong π–π interaction, greatly improving GNSs dispersion in water. The resultant GNSs exhibit a high production yield (∼100%), high dispersion concentration and excellent film formation ability. The electrical and thermal conductivities of the as-prepared graphene paper were up to 2385 S cm −1 and 1324 W m −1 K −1, respectively, superior to those of most previously reported graphene materials. This graphene paper with the superb electrical and thermal conduction properties also exhibits excellent mechanical flexibility and structure intensity during bending, which has potential usages in electronic packaging and high power thermal management.